MANAJEMEN PEMBELAJARAN PENDIDIKAN INKLUSI PADA ANAK BERKEBUTUHAN KHUSUS DI SDN KALIRUNGKUT-1 SURABAYA - Siti Auliyatus Sholawati (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2019)
This study aims to identify, explain and analyze: (1) Planning, (2) Organizing, (3) Implementation, and (4) Evaluation of inclusive education learning for children with special needs. The research approach uses descriptive qualitative using the case study method. Data collection was carried out through observation, interviews and document analysis. The results of the research are based on data analysis and observations in the field, namely: (1) Inclusive education learning planning begins with making syllabus, lesson plans, and PPI adjusted to the constraints of each student with special needs which will later regulate the process of implementing learning in regular classes. (2) Organizing inclusive education learning begins with grouping and dividing tasks for implementing the learning plan, namely homeroom teachers, field study teachers and special companion teachers who are tasked with accompanying students with special needs. (3) The implementation of inclusive education learning for children with special needs has a special service program for each student's disability according to the RPP and PPI that have been prepared, each learning process is always integrated with aspects of student development and some of them maximize the talents and interests of students with special needs. (4) Evaluation of inclusive education learning is carried out by providing a review of the implementation process that has taken place and the results of the assessment of student learning.